Lateral circumflex femoral artery pseudoaneurysm following transfemoral coronary intervention - Sri Satyavathi Davulury; Vinod Bhan (Journal of Clinical and Scientific Research)
Post-femoral access arterial injuries are well-known entities with attendant complications involving common femoral, superficial femoral and profunda femoris arteries, and rarely, pelvic vessel injuries were described. We report the case of pseudoaneurysm of the lateral circumflex femoral artery following percutaneous coronary angioplasty for unstable angina and left circumflex coronary artery stenting. The patient underwent open surgical repair for femoral pseudoaneurysm with uneventful recovery. To the best of our knowledge, this is the first reported case of pseudoaneurysm from the lateral circumflex femoral artery following percutaneous coronary intervention.